2007
DOI: 10.1111/j.1530-0277.2007.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of Ethanol‐Seeking Behavior Following Intravenous Self‐Administration in Wistar Rats

Abstract: Ethanol serves as a reinforcer when self-administered IV, and following extinction, ethanol-seeking behavior can be reinstated by ethanol-associated cues, ethanol priming, or a pharmacological stressor. Thus, reinstatement of ethanol-seeking behavior in animals with a history of IV ethanol self-administration may be a novel animal model of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 38 publications
2
37
1
Order By: Relevance
“…Interestingly, in both rats and monkeys, the a2-antagonist, yohimbine, induces reinstatement, acting like a stressor Shepard et al 2004;Gass & Olive 2007). In additional experiments, we determined that noradrenergic neurons arising from the lateral tegmental nuclei and projecting to the CeA and BNST were of primary importance in stress-induced reinstatement (Shaham et al 2000b).…”
Section: Stress-induced Reinstatementmentioning
confidence: 97%
“…Interestingly, in both rats and monkeys, the a2-antagonist, yohimbine, induces reinstatement, acting like a stressor Shepard et al 2004;Gass & Olive 2007). In additional experiments, we determined that noradrenergic neurons arising from the lateral tegmental nuclei and projecting to the CeA and BNST were of primary importance in stress-induced reinstatement (Shaham et al 2000b).…”
Section: Stress-induced Reinstatementmentioning
confidence: 97%
“…In addition, non-alcoholics tend to choose alcohol over other types of reinforcement and show increased alcohol consumption following an alcohol priming dose (Chutuape and de Wit 1994; de Wit and Chutuape 1993; Hobbs et al 2005). In preclinical animal models, an experimenter-administered priming dose of alcohol effectively reinstates alcohol-seeking behavior (Gass and Olive 2007; Le et al 1999; Le et al 1998; Vosler et al 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Many theories of addiction hypothesize that stress is one of the primary causes of relapse in human addicts (2,3). Using animal models, several laboratories have demonstrated that exposure to an acute stressor can effectively reinstate drug seeking of various drugs, including opiates, psychostimulants, alcohol, and nicotine (68)(69)(70)(71). Stress facilitates relapse by activating central CRF brain circuits.…”
Section: Effect Of Stress On the Addiction Cyclementioning
confidence: 99%